Sick Building Syndrome (SBS): unraveling the environmental enigma / Ahmad Marzuki Amiruddin Othman ... [et al.] - Othman, Ahmad Marzuki Amiruddin; Raja Ahmad, Raja Adzrin; Mustafa Kamal, Musmailina; Abd Mansor, Nor Hafizah (Universiti Teknologi MARA, Negeri Sembilan, 2024)
Sick Building Syndrome (SBS) is a term that has gained prominence in the last few decades. Some old buildings, for example, give us creeps due to their gloomy atmosphere, moldy and stained walls. In other cases, we might feel dizzy, claustrophobic and have difficulty breathing in crampy, confined lifts and offices. Have you ever felt uncomfortable and nauseous when using poorly maintained public toilets and facilities in unkempt train and bus stations? These symptoms might be attributed to the SBS phenomenon, where occupants experience various health-related symptoms linked to the time spent in a poorly maintained building (Mendes, 2014). The symptoms are often nonspecific and can vary widely, encompassing respiratory issues, headaches, eye, nose, and throat irritation, fatigue, and other discomforts. Female residents with a respiratory disease history and from lower-income families reported with more SBS symptoms (Shao, 2023).